Why I write - Owrwell, George (London Penguin Book, 1984)
Whether puncturing the lies of politicians, wittily dissecting the English character or telling unpalatable truths about war, Orwell's timeless, uncompromising essays are more relevant, entertaining and essential than ever in today's era of spin.
Keywords: Political and social views; Authorship